Brexit, race and migration. (February 2019) - Burrell, Kathy; Hopkins, Peter; Isakjee, Arshad; Lorne, Colin; Nagel, Caroline; Finlay, Robin; Nayak, Anoop; Benwell, Matthew C; Pande, Raksha; Richardson, Michael; Botterill, Katherine; Rogaly, Ben
This timely series of interventions scrutinises the centrality of race and migration to the 2016 Brexit campaign, vote and its aftermath. It brings together five individual pieces, with an accompanying introduction, which interrogate different facets of how race, migration and Brexit interconnect: an examination of the so-called left behinds and the fundamental intersections between geography, race and class at the heart of Brexit motivations and contexts; an exploration of arguably parallel and similarly complex developments in the US with the rise of populism and support for Donald Trump; an analysis of the role of whiteness in the experiences of East European nationals in the UK in the face of increased anti-foreigner sentiment and uncertainty about future status; a discussion of intergenerational differences in outlooks on race and immigration and the sidelining of different people and places in Brexit debates; and a studied critique of prevailing tropes about Brexit which create divisive classed and raced categories and seek to oversimplify broader understandings of race, class and migration. Taken together these articles, all arguing for the need to eschew easy answers and superficial narratives, offer important and opportune insights into what Brexit tells us about race and migration in contemporary UK.